Impacts of green growth policies on labour markets and wage income distribution. A general equilibrium application to climate and energy policies - Chateau, Jean; Bibas, Ruben; Lanzi, Elisa (Paris, 2018)
"This paper explores the consequences on the labour markets of structural changes induced by decarbonisation policies. These policies are likely going to have consequences on labour-income distribution given i) existing rigidities in the labour markets, and ii) their different impacts on sectors and on job categories. These policies are analysed in a general equilibrium modelling framework, which includes interlinkages between different sectors and regions as well as five different categories of workers."